Situation of Land Transportation in Nepal - Bhagat, Sadan Kumar (Tribhuvan University Journal, 2017)
There is a close relation between increment of transportation (roads and vehicles) and socio-economic development of the nation however, present condition of Nepal is discouraging. The study deals with present situation of land transportation, its problems with suggestions. An attempt has been made to point out causes and nature of road accidents, problems faced by general people and businessmen during travel and transportation of cargo. This study reveals that out of 29157 kilometers available road network only 12305 kilometers (42.20 %) road was black topped and the condition of road was miserable because there was no proper and regular repair and maintenance. Graveled roads were in very poor condition and in most of the roads and bridges were not constructed. Earthen roads were not suitable for travelling in rainy season. The buses run on long routes were found violating norm of keeping double drivers, the speed of vehicle remained higher than limit. They unnecessarily used loud or pressurize horn which had created noise pollution. The vehicles moved on graveled and earthen roads had been operating in poor condition. Vehicles were very old and damaged and only a few vehicles moved on certain routes. Vehicle accident incidences had frequently occurred in hilly areas where vehicles plunged down from the road and number of fatalities and injuries were found in double digit. The major reasons of accidents were high speed of vehicles, steering or brake failure, untrained and intoxicated drivers, driving by cleaner/conductor, continuous long duty hours of drivers, poor condition of vehicle, muddy and slippery roads, haphazard overtaking practice on single lane roads, lack of concentration of drivers on driving , non-observance of safety measures, traffic rules and signs, drove vehicle without wearing seat belt/helmet, kept more passengers than allowed/available seats, hung passengers on gate, backside and roof, loaded cargo beyond the limited weight and height respectively.